GENDER STEREOTYPES IN THE DISNEY MOVIE MOANA - Muin, Ince Maharani A.; Weda, Sukardi; Fitriyani, Fitriyani (Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
Disney's Moana is a story about the hardships Moana has as the island's new leader to protect it from darkness. Moana is adamant that she can save her island by bringing Te Fiti's heart back to its source. This study aims to identify the phenomenon of gender stereotypes found in the Disney movie Moana on the main character of the Disney movie Moana and describe how gender stereotypes apply through the characteristics in the Disney movie Moana which are represented by the main female character in the movie. The research method that researchers use is a qualitative research method, namely by watching the Disney Moana movie through the website, Disney Hotstar. The findings of this study demonstrate that Moana possesses eight traits, including optimism, high curiosity, daredevilry, independence, stubbornness, smarts, and open-mindedness. Additionally, Moana's actions as the primary characte or character in the movie mirror the prejudices that were attributed to her when the Disney movie Moana first came out. The two points in this instance where gender stereotypes are applied to the lead character of the Disney movie Moana are Moana's leadership qualities as a female and main character, which in this case can be proven by how Moana solves all the problems she faces without assistance from others, and Moana's struggle to obtain her freedom, which can be demonstrated by her achieving her desire to save Motunui Island from darkness and disaster